1998
DOI: 10.1046/j.1365-2249.1998.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Fas ligand (FasL) mRNA expression in peripheral blood mononuclear cells (PBMC) after major surgery

Abstract: FasL, which is expressed mainly on activated lymphocytes, can induce apoptosis (programmed cell death) of cells which express Fas. Fas/FasL interaction is primarily beneficial in maintaining immunological and physiological homeostasis by eliminating unnecessary cells. Dysregulation of the interaction, however, leads to tissue damage. We investigated how Fas/FasL levels changed after major surgery. The major aim of this study was to elucidate the involvement of the Fas/FasL system in postoperative inflammation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Activation of the apoptotic death program is thought to be a crucial mechanism, responsible for the lymphocyte depletion and immune suppression frequently seen in surgical patients immediately after surgery [2,11]. Surgeryinduced lymphocytopenia may be caused by lymphocyte redistribution, inappropriate cell death, or both [12,13]. Delogu et al showed that the rate of lymphocyte apoptosis is significantly increased in patients undergoing surgical stress [4].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the apoptotic death program is thought to be a crucial mechanism, responsible for the lymphocyte depletion and immune suppression frequently seen in surgical patients immediately after surgery [2,11]. Surgeryinduced lymphocytopenia may be caused by lymphocyte redistribution, inappropriate cell death, or both [12,13]. Delogu et al showed that the rate of lymphocyte apoptosis is significantly increased in patients undergoing surgical stress [4].…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible reasons for the low sensitivity of blood eosinophilia in the detection of ACR: Firstly, corticosteroids administered immediately following transplantation, and used for the treatment of ACR, are known to be eosinopenic (6), and these effects may be prolonged in patients with renal or hepatic insufficiency. Secondly, defects in cellular immunity associated with severe liver dysfunction (15), acute severe illness and major abdominal surgery (16) may suppress the eosinophil count in the presence of ACR. Thirdly, we show that blood eosinophilia is a particularly poor marker of ACR in the setting of hepatitis C virus infection and hypothesize that HCV may suppress the eosinophilic response (see later); it is therefore plausible that other viral infections such as hepatitis B virus, cytomegalovirus and herpes simplex virus may have similar suppressive effects on the eosinophil count and limit the sensitivity in the detection of ACR.…”
Section: Discussionmentioning
confidence: 99%
“…Such lymphocyte phenotypes and a significantly decreased Bcl-2 intracellular expression after surgery (significant on day 1 and 7) for pancreatic cancer may lead to an inappropriate cell apoptosis. A series of studies has demonstrated that circulating lymphocytes in the early postoperative period are susceptible to apoptosis, which may cause deletion of peripheral lymphocytes after surgery (Oka et al 1996;Sugimoto et al 1998). In the early postoperative period, surgical trauma under general anesthesia induces an intracellular perturbation on peripheral lymphocytes, resulting in both up-regulation of death-signaling factors (Fas, FasL) and down-regulation of survivalsignaling factors (Bcl-2).…”
Section: Discussionmentioning
confidence: 99%